Rational design of antisense oligonucleotides modulating the activity of TLR7/8 agonists. Issue 13 (16th June 2020) - Alharbi, Arwaf S; Garcin, Aurélie J; Lennox, Kim A; Pradeloux, Solène; Wong, Christophe; Straub, Sarah; Valentin, Roxane; Pépin, Geneviève; Li, Hong-Mei; Nold, Marcel F; Nold-Petry, Claudia A; Behlke, Mark A; et al.
Abstract: Oligonucleotide-based therapeutics have become a reality, and are set to transform management of many diseases. Nevertheless, the modulatory activities of these molecules on immune responses remain incompletely defined. Here, we show that gene targeting 2′- O -methyl (2′OMe) gapmer antisense oligonucleotides (ASOs) can have opposing activities on Toll-Like Receptors 7 and 8 (TLR7/8), leading to divergent suppression of TLR7 and activation of TLR8, in a sequence-dependent manner. Surprisingly, TLR8 potentiation by the gapmer ASOs was blunted by locked nucleic acid (LNA) and 2′-methoxyethyl (2′MOE) modifications. Through a screen of 192 2′OMe ASOs and sequence mutants, we characterized the structural and sequence determinants of these activities. Importantly, we identified core motifs preventing the immunosuppressive activities of 2′OMe ASOs on TLR7. Based on these observations, we designed oligonucleotides strongly potentiating TLR8 sensing of Resiquimod, which preserve TLR7 function, and promote strong activation of phagocytes and immune cells. We also provide proof-of-principle data that gene-targeting ASOs can be selected to synergize with TLR8 agonists currently under investigation as immunotherapies, and show that rational ASO selection can be used to prevent unintended immune suppression of TLR7. Taken together, our work characterizes the immumodulatory effects of ASOs to advance their therapeutic development.